2002
DOI: 10.1021/bi020193y
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Extracellular Domain and in the Membrane-Spanning Domains Interfere with Nicotinic Acetylcholine Receptor Maturation

Abstract: The deg-3(u662) mutation is a degeneration-causing mutation in a Caenorhabditis elegans nicotinic acetylcholine receptor. In a large screen for mutations that suppress the deleterious effects of this mutation we identified 32 mutations in the deg-3 gene. Among these, 11 are missense mutations, affecting seven residues within the extracellular domain or the membrane-spanning domains. All of these mutations greatly reduce the degeneration-causing activity of deg-3(u662). All but one of these mutations cause defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Reconstruction of the C. elegans nervous system from electron micrographs (EM) of serial sections suggested a relatively simple PVD architecture comprised of elongated, unbranched lateral processes projecting from anterior and posterior sides of each PVD soma and a single axon that grows downward to enter the ventral nerve cord (White et al, 1986). However, images of PVD obtained in the light microscope after immunostaining for a PVD-expressed membrane receptor (Halevi et al, 2002; Yassin et al, 2001; Yassin et al, 2002) or with a PVD-specific GFP reporter revealed a much more elaborate morphology with many additional dendritic branches(Tsalik and Hobert, 2003). Here we have used a bright PVD::GFP marker ( F49H12.4:: GFP) (Watson et al, 2008) (Fig 1) to reveal that PVD architecture is defined by a complex but well-ordered array of non-overlapping sister dendrites and that the creation of this structure involves a stereotypical series of branching decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Reconstruction of the C. elegans nervous system from electron micrographs (EM) of serial sections suggested a relatively simple PVD architecture comprised of elongated, unbranched lateral processes projecting from anterior and posterior sides of each PVD soma and a single axon that grows downward to enter the ventral nerve cord (White et al, 1986). However, images of PVD obtained in the light microscope after immunostaining for a PVD-expressed membrane receptor (Halevi et al, 2002; Yassin et al, 2001; Yassin et al, 2002) or with a PVD-specific GFP reporter revealed a much more elaborate morphology with many additional dendritic branches(Tsalik and Hobert, 2003). Here we have used a bright PVD::GFP marker ( F49H12.4:: GFP) (Watson et al, 2008) (Fig 1) to reveal that PVD architecture is defined by a complex but well-ordered array of non-overlapping sister dendrites and that the creation of this structure involves a stereotypical series of branching decisions.…”
Section: Resultsmentioning
confidence: 99%
“…It was assumed that screening for mutations that cause suppression of the deg‐3(u662) phenotype might identify genes, which are required for nAChR function. Several suppressor mutations were identified within the deg‐3 gene itself ( Halevi et al , 2002 ; Yassin et al , 2002 ). Other suppressor mutations were identified within des‐2 ( Halevi et al , 2002 ), which encodes a nAChR subunit (DES‐2) that co‐assembles with DEG‐3 ( Treinin et al , 1998 ; Yassin et al , 2001 ).…”
Section: Identification Of a Role For Ric‐3 In Nachr Maturationmentioning
confidence: 99%
“…Analysis of deg-3 mutants in combination with homology modelling of the DEG-3 receptor have suggested that several amino acid residues in the Nterminal region are important for correct receptor maturation, assembly and localization by, for example, maintaining correct protein folding. (84) The study of ligand-receptor interactions using site-directed and in silico mutagenesis has proven successful in implicating amino acid residues important in determining imidacloprid specificity to insect nAChRs over vertebrate receptors. (85) Thus, further studies of this kind, in combination with pharmacological analysis of nAChRs expressed in heterologous systems such as Xenopus oocytes, should greatly assist in the development of novel drugs/ chemicals for use in human health, animal health and agriculture.…”
Section: Deg-3/des-2mentioning
confidence: 99%